Morphology and chronology of diphyodont dentition in miniature pigs, Sus Scrofa. (16th May 2013) - Wang, F; Xiao, J; Cong, W; Li, A; Song, T; Wei, F; Xu, J; Zhang, C; Fan, Z; Wang, S
Abstract : Objective: There is little knowledge about the tooth replacement in large mammals. The aim of this study is to investigate the tooth replacement patterns in Chinese miniature pig (Sus Scrofa). Materials and Methods: The developmental patterns of mandibular successional and additional teeth from Chinese miniature pig before and after birth were investigated by microanatomy, immunohistochemistry, and cone beam computed tomography. Results: Secondary dental lamina for successional teeth was not visible until its predecessor progressed to late bell stage. Successional teeth reached early cap stage when their predecessor began to erupt. The development patterns and speed varied between anterior and posterior successional teeth. Additional molars, derived from the free end of additional dental lamina, initiated sequentially in mandible ramus, while previous additional molar progressed into late bell stage. Proliferating cells in the permanent primordium were distributed asymmetrically. Conclusions: Our findings identify the characteristic patterns about spatiotemporal morphogenesis of successional teeth in context of their predecessor and cascade initiation of additional molars in miniature pigs. Our study provides a basis toward better understanding the mechanisms underlying diphyodont replacement in human and also assists in tooth regeneration and tooth engineering in large animal.